Constitutional agencies and commissions - Garcia, Ramon M. (1978)
The 1973 Philippine Constitution provided for the creation of agencies and commissions, namely: the National Economic and Development Authority, the Civil Service Commission, the Commission on Elections and the Commission on Audit. Of the three Commission, the Civil Service Commission has been the object of most of the changes contained in the new Constitution. These changes were instituted as a response to the weaknesses of civil service such as overstaffed government machinery, corruption in the system of recruitment, personnel evaluation, and securing jobs. To curb these excesses, the purge of notoriously undesirable or corrupt personnel was undertaken and a special administrative court, the Sandigan Bayan, and its investigating unit, the Tanod Bayan, which would prosecute public personnel committing illegal acts were created. The emerging close relationship between the President and the Civil Service Commission has become an issue of the encroachment of the President on the independence of the Civil Service Commission postulated in the new Constitution. Moreover, the view of the present administration of the principles of separation of powers and checks and balances appears to be contrary to the letter and spirit of the new Constitution.
Keywords: Government agencies; Constitutional reform; Public administration